Gender roles in war: Zweiter Weltkrieg’s (World War II) homefront against battlefront in a woman in Berlin - Rokaiya, Iffat (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2022.